Insights into the Crystallization and Structural Evolution of Glycine Dihydrate by In Situ Solid‐State NMR Spectroscopy. (8th May 2018) - Cerreia Vioglio, Paolo; Mollica, Giulia; Juramy, Marie; Hughes, Colan E.; Williams, P. Andrew; Ziarelli, Fabio; Viel, Stéphane; Thureau, Pierre; Harris, Kenneth D. M.
Abstract: In situ solid‐state NMR spectroscopy is exploited to monitor the structural evolution of a glycine/water glass phase formed on flash cooling an aqueous solution of glycine, with a range of modern solid‐state NMR methods applied to elucidate structural properties of the solid phases present. The glycine/water glass is shown to crystallize into an intermediate phase, which then transforms to the β polymorph of glycine. Our in situ NMR results fully corroborate the identity of the intermediate crystalline phase as glycine dihydrate, which was first proposed only very recently. Abstract : Phasenumwandlungen : Nach Blitzkühlung einer wässrigen Glycinlösung wurde mittels In‐situ‐Festkörper‐NMR‐Spektroskopie die strukturelle Umwandlung der Glycin/Wasser‐Glasphase zu kristallinem Glycindihydrat und dann zum β‐Polymorph von wasserfreiem Glycin verfolgt. Mit dieser Strategie können die Bildung und strukturellen Eigenschaften der erst kürzlich beschriebenen kristallinen Dihydratphase von Glycin untersucht werden.